PSX-29 Intake, feed efficiency and carcass traits of Charolais and Holstein-Friesian steers offered a high-concentrate diet. (7th December 2018) - McGee, M; Kenny, D; Fitzsimons, C
Abstract: Due to the abolition of milk quotas in the European Union, expansion of the Irish dairy herd has meant that proportionately more beef is derived from dairy-bred compared to beef-bred animals. The objective was to determine intake, growth, feed efficiency and carcass traits of Charolais (CH) (n=92) compared to Holstein-Friesian (HF) (n=85) steers offered a high-concentrate, barley-based diet. Following a dietary adaptation period individual DM intake and live weight were measured over a 71 d finishing period. Data were statistically analysed using ANOVA; the model contained the fixed effect of breed. HF steers were 24 days older (P < 0.001) than CH, which reflects the mean calving dates of the national dairy and beef cow herds in Ireland. Compared to HF steers, CH were heavier (mid-test, 726 v. 659 kg, P < 0.001) and had greater (P = 0.07) daily live weight gain (1.37 v. 1.28 kg), lower daily DM intake on an absolute basis (11.5 v. 12.6 kg) and relative to live weight (15.8 v. 19.1 g/kg), and better G:F (0.12 v. 0.10, kg live weight gain/kg DM intake) (P < 0.001). In terms of body measurements, HF were significantly longer, taller, narrower and had deeper chests, and lower ultrasonically-assessed muscle depth than CH. Carcass weight was lighter (360 v. 442 kg, P < 0.001), and kill-out proportion (519 v. 617 g/kg, P < 0.01) and carcass conformation score (4.5 v 10.3, scale 1–15, P < 0.001) were poorer, for HF compared to CH. Carcass fat score (9.9, scale 1–15) did not differ (P > 0.05) between the breeds. Liver (P < 0.001) and empty rumen weight (P < 0.01) were lighter for CH than HF. In conclusion, the lighter, slower-growing HF consumed 0.10 more feed DM resulting in a substantially inferior feed efficiency compared to CH.